PAK Kinases Target Sortilin and Modulate Its Sorting - Pallesen, Lone Tjener (Mol Cell Biol, 2020)
The multifunctional type 1 receptor sortilin is involved in endocytosis and intracellular transport of ligands. The short intracellular domain of sortilin binds several cytoplasmic adaptor proteins (e.g., the AP-1 complex and GGA1 to -3), most of which target two well-defined motifs: a C-terminal acidic cluster dileucine motif and a YXXΦ motif in the proximal third of the domain. Both motifs contribute to endocytosis as well as Golgi-endosome trafficking of sortilin. The C-terminal acidic cluster harbors a serine residue, which is subject to phosphorylation by casein kinase. Phosphorylation of this serine residue is known to modulate adaptor binding to sortilin. Here, we show that the cytoplasmic domain of sortilin also engages Rac-p21-activated kinases 1 to 3 (PAK1-3) via a binding segment that includes a tyrosine-based motif, also encompassing a serine residue. We further demonstrate that PAK1-3 specifically phosphorylate this serine residue and that this phosphorylation alters the affinity for AP-1 binding and consequently changes the intracellular localization of sortilin as a result of modulated trafficking. Our findings suggest that trafficking of ligands bound to sortilin is in part regulated by group A PAK kinases, which are downstream effectors of Rho GTPases and are known to affect a variety of processes by remodeling the cytoskeleton and by promoting gene transcription and cell survival.